Evaluation of micro-ESR method with Westergren method for determination of erythrocyte sedimentation rate - Preet, Kamal; Anchinmane, Vyankatesh T.; Sankhe, Shilpa (International Journal of Research in Medical Sciences, 2018)
Background: Erythrocyte sedimentation rate (ESR) test provides valuable information in screening, diagnosis, as well as monitoring disease activity and therapeutic response in numerous health conditions. The most commonly used method for determination of ESR is Westergren method, which is time-consuming and requires a large amount of blood sample. There are several other methods, like Micro-ESR method which overcome the limitations of conventional Westergren method, hence the present study was performed to compare results of Westergren method with Micro-ESR method for determination of ESR. Methods: In the present study, blood samples from 100 patients were processed for ESR determination by Westergren method and Micro-ESR method. The results obtained were compared using Pearson’s correlation test. Results: The Westergren method was the reference method and the Micro-ESR method was testing method. The comparison was done between Micro- ESR method results (X-axis) and results of Westergren method (Y-axis). The slope of the regression line using linear regression was 1.010 with a y-intercept of -0.788. Statistical analysis demonstrated significant correlation of results of Micro-ESR method with Westergren method (r = 0.9977). Conclusions: Micro-ESR is a reliable and precise method for ESR measurement. The Micro- ESR method is simple to perform and requires very small volume of blood (0.2ml) as compared to conventional Westergren method. It can be potential useful tool in performing ESR determination especially for the patients with limitation of blood availability as pediatric patients and very old patients.